Desarrollo del repositorio de recursos educativos abiertos para la Universidad Virtual de Salud de Santiago de Cuba. - Guisande, Sulin Sam; Rodríguez Beltrán, Nancy María; de la Cruz Moreno, Maroibis; Ladoy, Lisbet Estrada (MEDISAN, 2024)
The use of digital technologies in teaching determines the development of new intellectual skills in students, which facilitates the application of investigation strategies, improves their capabilities in an integral way, helps them face the difficulties and demands of the current world and allows them to acquire more significant learning to have a good performance in the socio-educational environment. With a view to fulfilling the above, an institutional repository of open educational resources was developed for the Virtual Health University, based on the use of free and open-source technology tools that allow the standardization and interoperability among each of the repositories established in the National Health System, which will guarantee logic of academic organization.